Cerebral Ischemia Increases Small Ubiquitin-Like Modifier Conjugation within Human Penumbral Tissue: Radiological–Pathological Correlation - Bernstock, Joshua D.; Ye, Daniel G.; Griffin, Allison; Lee, Yang-ja; Lynch, John; Latour, Lawrence L.; Friedman, Gregory K.; Maric, Dragan; Hallenbeck, John M. (Frontiers in Neurology, 2018)
Post-translational modification by Small Ubiquitin-like MOdifier (SUMO) regulates myriad physiological processes within cells, and has been demonstrated to be highly activated in murine brains following cerebral ischemia. Numerous in vitro and murine in vivo studies have demonstrated that this increased SUMO-conjugation is an endogenous neuroprotective stress response that has potential in being leveraged to develop novel therapies for ischemic stroke. However, SUMO-activation has not yet been studied in post-stroke human brains, presenting a clear limitation in translating experimental successes in murine models to human patients. Accordingly, we herein present a case wherein the brain tissue of a stroke patient (procured shortly after death) was processed by multiplex immunohistochemistry to investigate SUMO activation.